Hydrophilic bile acids protect human blood-brain barrier endothelial cells from disruption by unconjugated bilirubin: an in vitro study - Palmela, Inês; Correia, Leonor; Silva, Rui F. M.; Sasaki, Hiroyuki; Kim, Kwang S.; Brites, Dora; Brito, Maria A. (Frontiers in Neuroscience, 2015)
Ursodeoxycholic acid and its main conjugate glycoursodeoxycholic acid are bile acids with neuroprotective properties. Our previous studies demonstrated their anti-apoptotic, anti-inflammatory and antioxidant properties in neural cells exposed to elevated levels of unconjugated bilirubin as in severe jaundice. In a simplified model of the blood-brain barrier, formed by confluent monolayers of a cell line of human brain microvascular endothelial cells, unconjugated bilirubin has shown to induce caspase-3 activation and cell death, as well as interleukin-6 release and a loss of blood-brain barrier integrity. Here we tested the preventive and restorative effects of these bile acids regarding the disruption of blood-brain barrier properties by unconjugated bilirubin in in vitro conditions mimicking severe neonatal hyperbilirubinemia and using the same experimental blood-brain barrier model. Both bile acids reduced the apoptotic cell death induced by unconjugated bilirubin, but only glycoursodeoxycholic acid significantly counteracted caspase-3 activation. Bile acids also prevented the upregulation of interleukin-6 mRNA, whereas only ursodeoxycholic acid abrogated cytokine release. Regarding barrier integrity, only ursodeoxycholic acid abrogated unconjugated bilirubin-induced barrier permeability. Better protective effects were obtained by bile acid pre-treatment, but a strong efficacy was still observed by their addition after unconjugated bilirubin treatment. Finally, both bile acids showed ability to cross confluent monolayers of human brain microvascular endothelial cells in a time-dependent manner. Collectively, data disclose a therapeutic time-window for preventive and restorative effects of ursodeoxycholic acid and glycoursodeoxycholic acid against unconjugated bilirubin-induced blood-brain barrier disruption and damage to human brain microvascular endothelial cells.